2017
DOI: 10.1213/ane.0000000000001778
|View full text |Cite
|
Sign up to set email alerts
|

Increased Perinatal Morbidity and Mortality Among Asian American and Pacific Islander Women in the United States

Abstract: Despite having a higher socioeconomic status, AAPI women had higher rates of maternal mortality during hospitalization for delivery. This increase persisted even after adjustment for factors known to affect peripartum outcomes. Further investigation is needed to better clarify the causes of racial differences in maternal morbidity and mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 43 publications
4
12
0
Order By: Relevance
“…Similarly, Bryant et al 7 observed racial differences in postpartum hemorrhage due to uterine atony requiring peripartum hysterectomy, but their models did not include hospital region, 7 which attenuated the present study’s observed association between race and peripartum hysterectomy among black women. The findings in the present study of a 2–3‐fold increased risk of maternal death for women of color after peripartum hysterectomy is similar to previously reported elevated rates of all‐cause pregnancy‐related mortality for these racial/ethnic groups 10,39 . The present study’s finding of higher odds of perioperative complications among non‐white peripartum hysterectomy recipients is also largely consistent with prior studies 7,10,40 and may point to differences in care.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Similarly, Bryant et al 7 observed racial differences in postpartum hemorrhage due to uterine atony requiring peripartum hysterectomy, but their models did not include hospital region, 7 which attenuated the present study’s observed association between race and peripartum hysterectomy among black women. The findings in the present study of a 2–3‐fold increased risk of maternal death for women of color after peripartum hysterectomy is similar to previously reported elevated rates of all‐cause pregnancy‐related mortality for these racial/ethnic groups 10,39 . The present study’s finding of higher odds of perioperative complications among non‐white peripartum hysterectomy recipients is also largely consistent with prior studies 7,10,40 and may point to differences in care.…”
Section: Discussionsupporting
confidence: 90%
“…The findings in the present study of a 2–3‐fold increased risk of maternal death for women of color after peripartum hysterectomy is similar to previously reported elevated rates of all‐cause pregnancy‐related mortality for these racial/ethnic groups 10,39 . The present study’s finding of higher odds of perioperative complications among non‐white peripartum hysterectomy recipients is also largely consistent with prior studies 7,10,40 and may point to differences in care. While previous work demonstrated that childbirth hospitalizations complicated by severe maternal morbidity were more costly than those without, those analyses included costs for hospitalizations where patients did not have peripartum hysterectomy 41 .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…동반질환 (Lindquist et al, 2014), (Grobman et al, 산과적 합병증 2014), Norhayati et al, 2016;Kominiarek et al, 2017;Siddiqui et al, 2017), 다태아 (Martin et al, 2016;Santana et al, 2016;Witteveen 제왕절개 et al, 2016), (Grobman et al, 2014;Lindquist 조산 et al, 2014;Norhayati et al, 2016), (…”
Section: 산경험mentioning
confidence: 99%